Advances in artificial intelligence – IBERAMIA 2018 : 16th Ibero-American Conference on AI, Trujillo, Peru, November 13-16, 2018, Proceedings /: 16th Ibero-American Conference on AI, Trujillo, Peru, November 13-16, 2018, Proceedings. (2018) - Unknown
No abstract available